Effects of phonophoresis with Arnica montana onto acute inflammatory process in rat skeletal muscles: An experimental study - Alfredo, Patricia P.; Anaruma, Carlos Alberto [UNESP]; Piao, Antonio C. S. [UNESP]; Joao, Silvia M. A.; Casarotto, Raquel A. (Elsevier B.V., 2009)
This study aimed at verifying the effects of phonophoresis associated with Arnica montana on the acute phase of an inflammatory muscle lesion. Forty Wistar male rats (300 +/- 50 g), of which the Tibialis Anterior muscle was surgically lesioned, were divided into four groups (n = 10 each): control group received no treatment; the ultrasound group (US) was treated in pulsed mode with 1-MHz frequency, 0.5 W/cm(2) intensity (spatial and temporal average - SATA), duty cycle of 1: 2 (2 ms on, 4 ms off, 50%), time of application 3 min per session, one session per day, for 3 days; the phonophoresis or ultrasound plus arnica (US+A) group was treated with arnica with the same US parameters plus arnica gel; and the arnica group (A) was submitted to massage with arnica gel, also for 3 min, once a day, for 3 days. Treatment started 24 h after the surgical lesion. on the 4th day after lesion creation, animals were sacrificed and sections of the lesioned, inflamed muscle were removed for quantitative (mononuclear and polymorphonuclear cell count) and qualitative histological analysis. Collected data from the 4 groups were statistically analyzed and the significance level set at p < 0.05. Results show higher mononuclear cell density in all three treated groups with no significant difference between them, but values were significantly different (p < 0.0001) when compared to control group's. As to polymorphonuclear cell density, significant differences were found between control group (p = 0.0134) and US, US+A and A groups; the arnica group presented lesser density of polymorphonuclear cells when compared (p = 0.0134) to the other groups. No significant difference was found between US and US+A groups. While the massage with arnica gel proved to be an effective anti-inflammatory on acute muscle lesion in topic use, these results point to ineffectiveness of Arnica montana phonophoresis, US having seemingly checked or minimized its anti-inflammatory effect. (C) 2008 Elsevier B. V. All rights reserved.
Keywords: Arnica montana; Muscle lesion; Phonophoresis; Therapeutic ultrasound